Analysis of Covid-19 impact on virtual hotel operation in Indonesia - Roz, Kenny; Riyanto, Dicky Wisnu Usdek; Marsudi, Marsudi; Salahudin, Salahudin (Technium Social Sciences Journal, 2021)
The Covid-19 pandemic outbreak had a devastating effect on the economic sector in Indonesia, especially in the tourism sector. This study aims to reveal the impact Covid-19 on the Indonesia tourism sector especially the virtual hotel operation. This research uses a qualitative approach and content analysis as data mapping of Indonesia online media content. Nvivo-12 plus software is used to manage and analyze the data. The results of this research pandemic covid 19 outbreaks have an impact on the economy of Indonesia and affect startup virtual hotel operations (especially Airy rooms) to the point of closing operations in Indonesia. This research provides some insight into future research opportunities in the new normal conditions in tourism sector operation